Selective Up-Regulation of Arginase-1 in Coronary Arteries of Diabetic Patients - Bagi, Zsolt; Feher, Attila; Dou, Huijuan; Broskova, Zuzana (Frontiers in Immunology, 2013)
Coronary artery disease (CAD) remains the leading cause of death in the Western societies. Diabetes mellitus (DM) is one of the highly prevalent diseases, which remarkably accelerates the development of CAD. Experimental evidence indicates that decreased bioavailability of coronary endothelial nitric oxide (NO) contributes to the development of CAD in DM. There are recent studies showing that a selective impairment of NO synthesis occurs in coronary arteries of DM patients, which is mainly due to the limited availability of endothelial NO synthase (eNOS) precursor, L-arginine. Importantly, these studies demonstrated that DM, independent of the presence of CAD, leads to selective up-regulation of arginase 1. Arginase 1 seems to play an important role in limiting L-arginine availability in the close proximity of eNOS in vessels of DM patients. This brief review examines recent clinical studies demonstrating the pathological role of vascular arginase 1 in human diabetes. Whether arginase 1, which is crucial in the synthesis of various fundamental polyamines in the body, will represent a potent therapeutic target for prevention of DM-associated CAD is still debated.